From Textile to Plastic: Architecture, Exhibition Design, and Abstraction (1930–1955) - Ottenhausen, Clemens (Artium Quaestiones, 2021)
This article investigates the growing proliferation of curtains and wall hangings as key elements in the design of art exhibitions in the years 1930–1955. To demonstrate how textiles were successfully employed as mediators on the threshold between architecture, design objects, and fine arts, I first examine the increasing use of curtains in the interwar period, Fascist Italy, and Nazi Germany to subsequently explore how the role of fabrics in both countries’ rationalist and neoclassicist architecture also played a significant part in exhibition design after the Second World War. I chart how the interest in textiles culminated in 1955, when glossy plastic curtains were integrated into the exhibition architecture at the first documenta in Kassel, Germany, one of the country’s most prestigious recurring art events to this day. During these politically turbulent decades, the exchange between exhibition designers in both countries was bound together by a profound reassessment of the relation between architecture, design, and art. The renewed consciousness of design as an integrated practice played a key role in 1930s architecture, also providing the foundation for the Bauhaus curriculum and the work of artists, designers, and architects (e.g., Wassily Kandinsky, Giuseppe Pagano, Le Corbusier, Carlo Scarpa, Willi Baumeister, Arnold Bode). I demonstrate that during this period textiles were essential for creating continuity between exhibitions and exhibits of vastly differing styles and contexts. The wall hangings, veils, and banners that were used as part of the monumental spaces created for the Fascist regimes in Italy and Germany were ultimately appropriated and turned into means to undermine the neoclassicist and rationalist style in a way that echoed, I argue, society’s neobaroque sensibility in the aftermath of World War II. Though the Federal Republic of Germany’s first two decades were characterized by the general will to educate its citizens in the aesthetics of internationalism, this effort and the concomitant return to the interwar period were accompanied by a strong resurgence in religiosity and desire for emotionally compelling experiences, which signify a partial disavowal of modernism’s most radical stipulations.